Diversamente mendicanti: L'esperienza dei frati eremiti di S. Giovanni Battista in Toscana fra XIII e XIV secolo - Pellegrini, Michele (Quaderni di storia religiosa medievale, 2025)
This essay casts light on a not hitherto known little "religio" - the hermit friars of St. John the Baptist - attested between the mid-13th and mid-14th centuries in few urban centers of central-southern Tuscany (Florence, Montepulciano, and mainly Siena): this group followed the Benedictine rule and somehow survived the "unio" of the Tuscan eremitical experiences started by the papacy in the 1240s; it received the papal approval in 1254 and disappeared in the middle of the following century, when its houses were incorporated into the Sylvestrine congregation. Surviving documents allow us to glimpse the ways of its presence and apostolate and its conventual economy, based on labor, begging and receipt of public subsidies and testamentary legacies. One episode also seems to point to a possible closeness of these "Fratres Baptistae" to themes and attitudes dear to some of the Franciscan Spirituals and irregular hermits groups, such as open contestation of priestly hegemony and lay-brothers marginalization, prevalent in the contemporary mendicant orders.